Analysis of Legal Responsibility for Environmental Impacts Due to Land Eviction in the Farm Road Construction Project in Tidore Islands City - Alauddin, Rusdin; Hasim, Dahlai; Sonta, Supri; Ikrima, Nur Aida; Sangaji, Irawan (Journal of Law, Politic and Humanities, 2025)
The title of this research is “Analysis of Legal Responsibility for Environmental Impacts Due to Land Eviction in the Farm Road Construction Project in Tidore Islands City”. The object of this research was the impacts of land eviction to construct farm roads in Tidore Islands City as well as the government’s legal responsibility. It aims to study the environmental impacts of land eviction in the construction of farm roads and the government's legal responsibility for its environmental impacts in Tidore Islands City. This study is an empirical legal study that uses a qualitative approach with observation, interview and documentation methods. Results show that the land eviction project activities in the Ake Sahu Environment, Tosa Village, East Tidore District have a very bad impact on the environment in the form of landslides in the eviction project area, floods that bring soil and rock material to the highway so that it greatly disrupts the access activities of the surrounding community, such impacts are not only caused by the eviction of the project but also the utilization activity (C excavation) by Cv. Mafututu Indah. The government has taken action to handle floods and landslides, then gave warnings and stopped the project.